Reflexiones sobre una Antropología «Nativa» - Lucila Gayané Tossounian (Amnis)
My paper examines the issues arisen, when researchers in Social Sciences carry out studies within the community they belong to. I will particularly deal with pieces of work that best exemplify the anthropological labour with immigrant communities; and in this perspective, I will question the notion of belonging that opens up, as well as the categories of reflexivity and subjectivity involved in the research processes. In this way, I account for and reflect on the special relation there is with the “object of study” in those cases. Anthropology allows exploring the native factor, which appears in this kind of studies, and takes into account the ways in which the so-called “native” anthropologists are conceived. The subjects of study are not the only ones to be sumitted to multiple identifications; we, as researchers and social actors, can belong to the communities we study in different ways, and be “native” in different moments and places. Therefore, identity should not be essentialized – neither that of natives nor of those who study them.